Evaluation of the flipped classroom approach in a veterinary professional skills course - Moffett J; Mill AC (Advances in Medical Education and Practice, 2014)
Jenny Moffett,1 Aileen C Mill2 1Ross University School of Veterinary Medicine, West Farm, St Kitts, West Indies; 2Modelling Suite, School of Biology, Newcastle University, Newcastle upon Tyne, UK Background: The flipped classroom is an educational approach that has had much recent coverage in the literature. Relatively few studies, however, use objective assessment of student performance to measure the impact of the flipped classroom on learning. The purpose of this study was to evaluate the use of a flipped classroom approach within a medical education setting to the first two levels of Kirkpatrick and Kirkpatrick's effectiveness of training framework. Methods: This study examined the use of a flipped classroom approach within a professional skills course offered to postgraduate veterinary students. A questionnaire was administered to two cohorts of students: those who had completed a traditional, lecture-based version of the course (Introduction to Veterinary Medicine [IVM]) and those who had completed a flipped classroom version (Veterinary Professional Foundations I [VPF I]). The academic performance of students within both cohorts was assessed using a set of multiple-choice items (n=24) nested within a written examination. Data obtained from the questionnaire were analyzed using Cronbach's alpha, Kruskal–Wallis tests, and factor analysis. Data obtained from student performance in the written examination were analyzed using the nonparametric Wilcoxon rank sum test. Results: A total of 133 IVM students and 64 VPF I students (n=197) agreed to take part in the study. Overall, study participants favored the flipped classroom approach over the traditional classroom approach. With respect to student academic performance, the traditional classroom students outperformed the flipped classroom students on a series of multiple-choice items (IVM mean =21.4±1.48 standard deviation; VPF I mean =20.25±2.20 standard deviation; Wilcoxon test, w=7,578; P<0.001). Conclusion: This study demonstrates that learners seem to prefer a flipped classroom approach. The flipped classroom was rated more positively than the traditional classroom on many different characteristics. This preference, however, did not translate into improved student performance, as assessed by a series of multiple-choice items delivered during a written examination. Keywords: active learning, assessment, didactic, flipped classroom, lecture, professional skills, student perception